Role of traditional food knowledge (TFK) in MALAY community towards festive cuisine sustainability / Dr. Norazmir Md Nor … [et al.] - Md Nor, Norazmir; Mohd Zahari, Mohd Salehuddin; Md Sharif, Mohd Shazali; Ishak, Noriza; Muhammad, Rosmaliza (Research Management Institute (RMI), 2013)
Traditional food knowledge (TFK) refers to the cultural tradition of sharing food provisioning skills, techniques and cultural beliefs from generation to generation. Traditional food knowledge can be a means of asserting cultural identity, particularly for specific cultural groups; transmitting this knowledge may contribute to personal skills that relate to food security and personal nutrition and enhanced community capacity. Traditional food knowledge (TFK) is a concept to acknowledge the importance of the relationship between traditional food cultures and healthy communities. Although TFK relates to all stages of food provisioning, particular attention are focused to cultural education, where TFK are suppose to be transmitted to the new generations. This transmission will not continue if both the process of deskilling in a modern commoditized food system and societal fragmentation facilitate consumption of convenience food commodities over localized production and provisioning. Traditional food is found to have a unanimously positive general image across Europe. In Malaysia, there are similar development happened but cannot be proved due limited publication that highlight the issues on traditional food knowledge (TFK) and heritance. To date, no research has been conducted in Malaysia on Traditional Food Knowledge (TFK) especially in Malay food. Traditional foods have ever evolved and always are part of any culture of races. Preserving the traditional food knowledge is crucial and it contributes to cultural identities which are supposed to be heritance for the next generations. Unfortunately, research on traditional food knowledge (TFK) is limited. Many factors have influenced the fact that traditional Malay food knowledge are not been well preserve and heritance, but there are very few studies to document this work. The purpose of the study is to explore the transmission of traditional Malay foods practices through generations.